Medical Director Responsibilities to the ESRD Network - DeOreo, Peter B. (Clin J Am Soc Nephrol, 2015)
The 18 regional ESRD Networks are established in legislation and contract with the Centers for Medicare and Medicaid Services to improve the quality and safety of dialysis, maximize patient rehabilitation, encourage collaboration among and between providers toward common quality goals, and improve the reliability and the use of data in pursuit of quality improvement. The Networks are funded by a $0.50 per treatment fee deducted from the reimbursement to dialysis providers, and their deliverables are determined by a statement of work, which is updated in a new contract every 3 years. The Conditions for Coverage require dialysis providers to participate in Network activities, and failure to do so can be the basis for sanctions against the provider. However, the Networks attempt to foster a collegial relationship with dialysis facilities by offering tools, educational activities, and other resources to assist the facilities in meeting the evolving requirements by the Centers for Medicare and Medicaid Services on the basis of national aims and domains for quality improvement in health care that transcend the ESRD program. Because of his/her responsibility for implementing the quality assessment and performance improvement activities in the facility, the medical director has much to gain by actively participating in Network activities, especially those focused on quality, safety, patient grievance, patient engagement, and coordination of care. Membership on Network committees can also foster the professional growth of the medical director through participation in quality improvement activity development and implementation, authorship of articles in peer-reviewed journals, creation of educational tools and presentations, and application of Network-sponsored materials to improve patient outcomes, engagement, and satisfaction in the medical director’s facility. The improvement of care of patients on dialysis will be beneficial to the facility in achieving its goals of quality, safety, and financial viability.